Could distal variants in ALG13 lead to atypical clinical presentation? - Accogli, Andrea; Radenkovic, Silvia; Ranatunga, Wasantha; Ligezka, Anna N.; Rivière, Jean-Baptiste; Morava, Eva; Trakadis, Yannis (European journal of medical genetics, 2022)
Congenital disorders of glycosylation (CDG) represent a wide range of some 150 inherited metabolic diseases, continually expanding in terms of newly identified genes and the heterogeneity of clinical and molecular presentations within each subtype. Heterozygous pathogenic variants in ALG13 are associated with early-onset epileptic encephalopathy, typically in females. The majority of subjects described so far harbour one of the two recurrent pathogenic variants, namely p.(Asn107Ser) and p.(Ala81Thr) in the C-terminal glycosyltransferase domain. We report a novel ALG13 variant (c.1709G > A, p.(Gly570Glu)) in an adult female with unremarkable past developmental and medical history, except for mild kinetic tremor. Our proband presented with acute onset of neurological and psychiatric features, along with liver dysfunction, during pregnancy, all of which gradually resolved after delivery. The proband's newborn baby died at 22 days of life from neonatal liver disease, due to gestational alloimmune liver disease (GALD). Functional assessment on fibroblasts derived from our case showed alterations in 2 of 3 cellular glycosylation markers (LAMP2, Factor IX), suggesting a functional effect of this novel ALG13 variant on glycosylation. This paper raises the possibility that variants outside the glycosyltransferase domain may have a hypomorphic effect leading to atypical clinical manifestations.